Are there spillovers from China on the global energy-growth nexus? Evidence from four world regions - Luís Miguel Marques; José Alberto Fuinhas; António Cardoso Marques (Economies, 2019)
This paper analyses China's energy consumption and economic growth spillover effects on four world regions: (i) America (North and South); (ii) Europe and Central Asia; (iii) Asia Pacific; and (iv) Africa and the Middle East. An annual aggregated time series by world region, from 1970 to 2016, and an autoregressive distributed lag (ARDL) approach were used. The results are consistent with the feedback hypothesis in the short run. With regard to the long run, feedback is present in America and the Asia Pacific. In Europe and Central Asia and in Africa and the Middle East, the results are consistent with the conservation hypothesis. Additionally, China's spillover effects on the world energy-growth nexus are essentially a long-run phenomenon, with impacts on Europe and Central Asia, Asia Pacific, and Africa and the Middle East. Accordingly, policy-makers should be aware that China's policies may have impact around the world, which indirectly may cause a restriction in economic growth.This paper analyses China's energy consumption and economic growth spillover effects on four world regions: (i) America (North and South); (ii) Europe and Central Asia; (iii) Asia Pacific; and (iv) Africa and the Middle East. An annual aggregated time series by world region, from 1970 to 2016, and an autoregressive distributed lag (ARDL) approach were used. The results are consistent with the feedback hypothesis in the short run. With regard to the long run, feedback is present in America and the Asia Pacific. In Europe and Central Asia and in Africa and the Middle East, the results are consistent with the conservation hypothesis. Additionally, China's spillover effects on the world energy-growth nexus are essentially a long-run phenomenon, with impacts on Europe and Central Asia, Asia Pacific, and Africa and the Middle East. Accordingly, policy-makers should be aware that China's policies may have impact around the world, which indirectly may cause a restriction in economic growth.
Keywords: C32; E03; O11; Q43; 330; ARDL; China’ s spillover effects; economic growth; energy-growth nexus; primary energy consumption